Efficient allocation of limited resources at the start of entrepreneurial activity ("Journal "U". Economy. Management. Finance.", 2025)
The article focuses on the strategic allocation of limited financial, human, and temporal resources using tools such as resource audits, activity prioritization, adaptive budgeting, and management methodologies. It examines a holistic approach to organizing economic processes in which resource allocation is based on value and risk analysis. This approach enhances business resilience, accelerates time-to-market, and reduces the likelihood of inefficient expenditures.
Keywords: startup; resource management; outsourcing; Lean Startup; MVP (Minimum Viable Product); ABC analysis; efficiency; entrepreneurship